2016
DOI: 10.1007/s10612-016-9336-5
|View full text |Cite
|
Sign up to set email alerts
|

Weapon-Carrying Among Young Men in Glasgow: Street Scripts and Signals in Uncertain Social Spaces

Abstract: Our work contributes through a cultural criminological perspective to a contextualised knowledge of street violence and its constructed meanings; uncertainty, familiarity and strangeness in spaces of urban disadvantage as perceived by Scottish white youths are examined. Youth criminal and antisocial behaviour associated with knifecarrying is widely reported and structures political and media discourses which classify street culture. In our article we argue that a particular symbolic construction of social spac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 28 publications
1
13
1
Order By: Relevance
“…Pre-placement of knives within the shrubbery of a housing estate or block of flats demonstrates ability to risk assess and control the environment. Holligan et al (2016) and Winlow and Hall (2009) identified something similar from their interview participants who were prepared to strike first and act pre-emptively. Recent expansion of the social field suggests that this assertion, once limited to interpretations of the physical field boundary (gang turf), is now open to wider interpretation.…”
Section: Agency and Taking Controlmentioning
confidence: 95%
See 2 more Smart Citations
“…Pre-placement of knives within the shrubbery of a housing estate or block of flats demonstrates ability to risk assess and control the environment. Holligan et al (2016) and Winlow and Hall (2009) identified something similar from their interview participants who were prepared to strike first and act pre-emptively. Recent expansion of the social field suggests that this assertion, once limited to interpretations of the physical field boundary (gang turf), is now open to wider interpretation.…”
Section: Agency and Taking Controlmentioning
confidence: 95%
“…In some ways the normalisation script is bolstered by local neighbourhood passivity and inactivity, or at times a casualised acquiescence to normalised violence which can be read as condoning knife-carrying for protection but which simultaneously generates wider forms of criminal agency. Holligan et al (2016) reported on one interviewed participant who utilised the discourse of Glasgow as 'stab capital of the world' to normalise his weapon-carrying.…”
Section: 'It Depends On What Scale You Want Man Like Violence To Usmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior research has documented how reputations for violence earned in gangs could lead to opportunities for employment in the illicit economy (Holligan, McLean and Deuchar ), and how gangs formed part of the same street culture that more organised criminal enterprise in Scotland grew out of (McLean ; McLean, Densley and Deuchar ). In some cases, gangs provided a pathway into more organised forms of criminality (Fraser ).…”
Section: Organised Crime In Scotlandmentioning
confidence: 99%
“…In some British cites, the demise of employment opportunities and weakening of community cohesion will trigger strain that may surface in recourse to the use of violence as a form of street capital enabling criminal governance. Local youths may also respond to the fear of crime by carrying weapons for status and protection (Holligan et al, 2017). Without the availability of recourse to the legal system, grievances and personal slights arising in criminal networks are resolved through codes of violent retribution and notions of natural justice (Coomber and Moyle, 2017; Densley, 2013).…”
Section: Introductionmentioning
confidence: 99%